Estimation Some Antioxidants Enzymes in Stress Patients in Babylon City - Sahar Saadi1 , Rasha Hashim Hussein2 , Saadi Mohammed3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oxidative stress can be defined as an increase in oxidative parameters or a decline in antioxidant defense mechanisms. Superoxide dismutase (SOD) and catalase (CAT) are antioxidant enzymes. They areresponsible for eliminating free radicals like superoxide and hydrogen peroxide, and they stand forantioxidant defense mechanisms an entire of fifty patients and twenty five control subjects were collected between April to August 2019 several physiological parameters were calculable similar to (SOD, and CAT). The results of present study illustrated that the patients groups, had greater significant differences (P? 0.05) levels of SOD, and CAT in contrast with control groups result at significant differences (P? 0.05).